Musculoskeletal stiffness changes linearly in response to increasing load during walking gait. Issue 6 (13th April 2015) - Caron, Robert R.; Lewis, Cara L.; Saltzman, Elliot; Wagenaar, Robert C.; Holt, Kenneth G.
Abstract Development of biologically inspired exoskeletons to assist soldiers in carrying load is a rapidly expanding field. Understanding how the body modulates stiffness in response to changing loads may inform the development of these exoskeletons and is the purpose of the present study. Seventeen subjects walked on a treadmill at a constant preferred walking velocity while nine different backpack loading conditions ranging from 12.5% to 40% bodyweight (BW) were introduced in an ascending and then descending order. Kinematic data were collected using Optotrak, a 3D motion analysis system, and used to estimate the position of the center of mass (COM). Two different estimates of stiffness were computed for the stance phase of gait. Both measures of stiffness were positively and linearly related to load magnitudes, with the slopes of the relationships being larger for the descending than the ascending conditions. These results indicate that changes in mechanical stiffness brought about in the musculoskeletal system vary systematically during increases in load to ensure that critical kinematic variables measured in a previous publication remain invariant (Caron et al., 2013). Changes in stiffness and other kinematics measured at the 40% BW condition suggest a boundary in which gait stiffness control limit is reached and a new gait pattern is required. Since soldiers are now carrying up to 96% of body weight, the need for research with even heavier loads is warranted. These findings have implications on the development of exoskeletons to assist in carrying loads.